(3ebGdI aj CUfGa GdeRGLs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s ((3Ydi Hf EHQGgje Hf CMeO GdJLjHi s)
(3ChdgG (B:s
(3GdZQV ef gPG Gdbhd Cf jaMU Yf YOO CUfGa GdeRGLGJ ai fhY ef CfhGY GdCLSGe GdeJTGHgI GdCLRGA ShGA cGfJ LRA s
(3BNQgG (B:s
(3GfbVJ ebGdI Gdabjg CHj GdhdjO Hf QTO ai CUfGa GdeRGL s
(3Vef eLehY , JQJjHgG (B: (3ef U (B59 - (3U(B64s
(3GfXQgG eY JdNjU cJGH GdMejGJ Qbe (B" 423"s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B318 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B313s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B242 s
Keywords: (3GdWHs